Cross-National Differences in Consumer Satisfaction: Mobile Services in Emerging and Developed Markets. Issue 2 (June 2015) - Morgeson, Forrest V.; Sharma, Pratyush Nidhi; Hult, G. Tomas M.
As firms attempt revenue growth through expansion into international markets, research on the potentially differential nature of consumer perceptions across national markets has become increasingly important. The authors advance the customer satisfaction literature by comparing customer perceptions in the wireless services industry across the national markets of Barbados, Singapore, Turkey, the United Kingdom, and the United States. This five-country context provides a unique opportunity for understanding how customers differ across markets because the data encompass consumers in disparate national markets (e.g., small/large, developing/developed, culturally heterogeneous) but include perceptions regarding a ubiquitous and increasingly commoditized service (wireless services). Focusing on emerging- versus developed-market comparisons, the findings provide important insights into unique differences in customer perceptions, including the greater importance of quality relative to value in influencing satisfaction in developed markets and the lesser importance of satisfaction in influencing customer loyalty in emerging markets.